\(a)|x+\frac{1}{5}|-4=-2\)                          
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

5 tháng 2 2019

a) \(\left|x+\frac{1}{5}\right|-4=-2\)

\(\Leftrightarrow\left|x+\frac{1}{5}\right|=-2+4\)

\(\Leftrightarrow\left|x+\frac{1}{5}\right|=2\)

Xét 2 trường hợp:

TH1: \(x+\frac{1}{5}=-2\)

\(\Leftrightarrow x=-2-\frac{1}{5}\)

      \(x=-\frac{11}{5}\)

TH2: \(x+\frac{1}{2}=2\)

\(\Leftrightarrow x=2-\frac{1}{5}\)

      \(x=\frac{9}{5}\)

\(\Rightarrow\orbr{\begin{cases}x=-\frac{11}{5}\\x=\frac{9}{5}\end{cases}}\)

25 tháng 8 2020

a) \(\frac{4}{9}x+\frac{2}{5}-\frac{1}{3}x=\frac{2}{9}-\frac{1}{4}x\)

\(\Leftrightarrow\frac{13}{36}x=-\frac{8}{45}\)

\(\Rightarrow x=-\frac{32}{65}\)

b) \(\left(\frac{2}{3}x-\frac{1}{2}\right).\left(-\frac{2}{3}\right)+\frac{1}{5}=-\frac{3}{4}\)

\(\Leftrightarrow-\frac{4}{9}x+\frac{1}{3}+\frac{1}{5}=-\frac{3}{4}\)

\(\Leftrightarrow\frac{4}{9}x=\frac{77}{60}\)

\(\Rightarrow x=\frac{231}{80}\)

25 tháng 8 2020

a) \(\frac{4}{9}x+\frac{2}{5}-\frac{1}{3}x=\frac{2}{9}-\frac{1}{4}x\)

=> \(\frac{4}{9}x-\frac{1}{3}x+\frac{2}{5}-\frac{2}{9}+\frac{1}{4}x=0\)

=> \(\left(\frac{4}{9}x-\frac{1}{3}x+\frac{1}{4}x\right)+\left(\frac{2}{5}-\frac{2}{9}\right)=0\)

=> \(\frac{13}{36}x+\frac{8}{45}=0\)

=> \(\frac{13}{36}x=-\frac{8}{45}\)

=> \(x=-\frac{32}{65}\)

b) \(\left(\frac{2}{3}x-\frac{1}{2}\right)\cdot\frac{-2}{3}+\frac{1}{5}=\frac{-3}{4}\)

=> \(\left(\frac{2}{3}x-\frac{1}{2}\right)\cdot\frac{-2}{3}=-\frac{19}{20}\)

=> \(\frac{2}{3}x-\frac{1}{2}=\left(-\frac{19}{20}\right):\left(-\frac{2}{3}\right)=\left(-\frac{19}{20}\right)\cdot\left(-\frac{3}{2}\right)=\frac{57}{40}\)

=> \(\frac{2}{3}x=\frac{57}{40}+\frac{1}{2}=\frac{77}{40}\)

=> \(x=\frac{77}{40}:\frac{2}{3}=\frac{77}{40}\cdot\frac{3}{2}=\frac{231}{80}\)

\(\frac{3}{4}x-\frac{2}{3}.\left(\frac{3}{5}x-\frac{6}{5}\right)=\frac{1}{7}-\frac{2}{9}x\)

\(\frac{3}{4}x-\frac{2}{5}x+\frac{4}{5}=\frac{1}{7}-\frac{2}{9}x\)

\(\left(\frac{3}{4}-\frac{2}{5}\right)x+\frac{4}{5}=\frac{1}{7}-\frac{2}{9}x\)

\(\left(\frac{15}{20}-\frac{8}{20}\right)x+\frac{4}{5}=\frac{1}{7}-\frac{2}{9}x\)

\(\frac{7}{20}x+\frac{4}{5}=\frac{1}{7}-\frac{2}{9}x\)

\(\frac{1}{7}-\frac{4}{5}=\frac{2}{9}x-\frac{7}{20}x\)

\(\frac{5}{35}-\frac{28}{35}=\left(\frac{2}{9}-\frac{7}{20}\right)x\)

\(\frac{-23}{35}=\left(\frac{40}{180}-\frac{63}{180}\right)x\)

\(\frac{-23}{180}x=\frac{-23}{35}\)

\(x=\frac{-23}{35}:\frac{-23}{180}\)

\(x=\frac{-23}{35}.\frac{180}{-23}\)

\(x=\frac{180}{35}\)

Vậy \(x=\frac{180}{35}\)

Chúc bạn học tốt

1 tháng 4 2019

A=1+(2-3-3+5)+(6-7-8+9)+....+(98-99-100+101)+102

=1+0+0+....+102=103

b) |1-2x|>7

=> 1-2x>7 hoặc 1-2x<-7

=> 2x<-6 hoặc 2x>8

=> x<-3 hoặc x>4

20 tháng 8 2020

\(\frac{5}{6}x+\frac{1}{2}-\frac{1}{3}x=0.75x-\frac{7}{8}\)

\(\frac{5}{6}x-\frac{1}{3}x-\frac{3}{4}x=-\frac{7}{8}-\frac{1}{2}\)     ( 3/4x là 0,75x nha)

\(x\times\left(\frac{10}{12}-\frac{4}{12}-\frac{9}{12}\right)=-\frac{7}{8}-\frac{4}{8}\)

\(x\times\left(-\frac{3}{12}\right)=-\frac{11}{8}\Rightarrow x=\frac{11}{8}\div\left(-\frac{3}{12}\right)=-\frac{11}{2}\)

15 tháng 9 2020

                                                                                      Bài giải

\(\frac{2}{7}x+\frac{5}{9}=\frac{1}{2}x+\frac{3}{4}\)

\(\frac{2}{7}x-\frac{1}{2}x=\frac{3}{4}-\frac{5}{9}\)

\(-\frac{5}{14}x=\frac{7}{36}\)

\(x=\frac{7}{36}\text{ : }\frac{-5}{14}\)

\(x=-\frac{49}{90}\)

15 tháng 9 2020

\(\frac{2}{7}x+\frac{5}{9}=\frac{1}{2}x+\frac{3}{4}\)

\(\frac{2}{7}x-\frac{1}{2}x=\frac{3}{4}-\frac{5}{9}\)

\(x.\left(\frac{2}{7}-\frac{1}{2}\right)=\frac{7}{36}\)

\(x.-\frac{3}{14}=\frac{7}{36}\)

\(x=\frac{7}{36}:-\frac{3}{14}\)

\(x=-\frac{49}{54}\)

vậy \(x=-\frac{49}{54}\)

27 tháng 9 2019

a)\(\left(\frac{4}{5}\right)^{2x+7}=\left(\frac{4}{5}\right)^4\)

=> 2x + 7 = 4 

     2x        = 4 - 7 

     2x        = -3

       x        = -3 : 2

       x         = -1,5

   Vậy x = -1,5